Techniques for transcatheter retrieval of the occlutech ASD device United Kingdom–European multicenter report. Issue 4 (10th November 2016) - Shebani, Suhair O; Rehman, Rizwan; Taliotis, Demetris; Magee, Alan; Hayes, Nicholas J; Baspinar, Osman; Martínez, Zunzunegui; Haas, Nikolaus; Duke, Christopher
Abstract : Aims: To gather current experience in Occlutech ASD device retrieval, to determine whether snaring is an effective technique and to highlight alternative retrieval techniques; Methods and Results: United Kingdom and European Occlutech ASD device implanters reported their experience in dealing with device embolization and retrieval. Six operators reported 12 retrieval cases. Retrieval was successful in 92% (11/12), although in most cases it was not straightforward and required multiple attempts using different techniques and equipment. When each different technique or equipment combination was considered separately, there were a total of 23 retrieval attempts. Fifteen attempts involved snaring the ball on the right atrial disc of the device ("the RA pin"). In 12/15 of these attempts the snare slipped off the RA pin. In 8/15 attempts snaring eventually failed. In two cases retrieval was facilitated by elongating the device in a blood vessel. In three cases retrieval was achieved by grasping the RA pin with the jaws of the Occlutech Flex II delivery cable; Conclusions: Snares do not grip the RA pin sufficiently to reliably retrieve the device. Funnelling the device into a blood vessel or grasping the RA pin with the jaws of the delivery cable may be successful alternatives. © 2016 Wiley Periodicals, Inc.